Appraising the Inclusive Definition of Workplace 'Violence' - Waddington, Peter A. J. (The British journal of criminology, 2005)
This article examines the limits to which inclusive' definitions of violence' can be usefully employed. It does so within the context of research into violence, threats and intimidation experienced in the workplace by police officers and social care professionals Accident and Emergency staff, mental health professionals, and social workers. Data were obtained from in-depth cognitive interviewing of 54 police officers and 62 social-care professionals who believed that they had recently suffered such attacks in the course of their work. What emerges is an enormously broad spectrum of behaviour that is experienced as violent, threatening or intimidating. It is argued that to stretch terms like violence' to cover such an array of experience is confusing, ultimately self-defeating and may create more problems than it resolves. The article concludes that researchers need to differentiate between episodes of violence' and suggests a set of criteria that should guide this enterprise